Revision of the Neotropical genus Coroichlorops Paganelli 2002 (Diptera: Chloropidae) - Riccardi, Paula Raile; Amorim, Dalton De Souza (Zootaxa, 2016)
Coroichlorops is a monotypic genus of Chloropini known to occur only in South America. The type species, C. yungas (Sabrosky & Paganelli), is formally known only from the holotype, collected in Bolivia. The male genitalia of the genus has peculiar prolonged, forceps-like surstyli. Two additional species of the genus, C. plaumanni sp. nov. and C. antennatus sp. nov., are formally described and illustrated here, and a key to the species of the genus is provided. The atypical flat arista of C. antennatus sp. nov. is also found in the Mepachymerini genus Sagareocerus and its implications are discussed.